Capturing the Invisible - Kirsi Laurén; Tiina Seppä; Juhana Venäläinen (Svetovi)
This article explores how digital devices shape aesthetic perceptions and interactions with fragile Finnish mires. Through senso-digital walking interviews, it examines how technologies like mobile cameras, social media, and navigation apps influence experiences of mires. Digital devices provide new ways to capture and share mire aesthetics and also mediate sensory interactions, allowing users to engage with the mires’ visual and ecological nuances. The role of digital tools in nature encounters highlights the evolving relationships between technology, perception, and place.